From the Editors: Introduction to Managing Supply Chains Beyond Covid‐19 ‐ Preparing for the Next Global Mega‐Disruption. Issue 1 (6th January 2021) - Flynn, Barbara; Cantor, David; Pagell, Mark; Dooley, Kevin J.; Azadegan, Arash
Abstract : The COVID‐19 pandemic has forced supply chain management researchers and practitioners to question many of our firmly held assumptions about the discipline. Perhaps the most interesting question is, where does supply chain management go from here? This issue of the Journal of Supply Chain Management begins to answer that question via a combination of invited essays and a regular submission. We consider this issue as only a starting point, and we hope to see its impact on future research on mega‐disruptions in supply chains.